Induction and regulation of glutathione transferases in wheat species exposed to PEG induced osmotic stress - Gallé, Ágnes (Acta Biologica Szegediensis, 2011)
The large and variable family of glutathione transferases (GST) has several functions in the stress response mechanisms. Our aim was to define the roles of different GST types in defence during osmotic stress conditions in wheat seedlings and to characterise their regulation by the stress hormone abscisic acid (ABA). Two wheat cultivars with different drought tolerance ability were exposed to 400 mOsm polyethylene glycol induced osmotic stress for one week. The hyperosmolarity of the nutrient solution increased the GST activity and the transcript amount of the selected tau group GSTs in the drought tolerant Kobomugi and moderately drought tolerant GK Öthalom cultivars. The role of abscisic acid in the regulation of GST expression was examined by the inhibition of ABA biosynthesis pathway with fluridone. The tau group GST expression of the two cultivars responded differently to the ABA biosynthesis inhibition.